Psychische Störungen und weibliche Infertilität = Mental disorders and female infertility - Schweiger, Ulrich; Wischmann, Tewes; Strowitzki, Thomas (Der Nervenarzt, 2012)
SummaryApproximately 5-10% of women in the reproductive years are affected by infertility which is associated with depression, anxiety and disturbed eating behavior. Part of this association can be explained by the emotional stress resulting from infertility. As mental disorders, such as depressive disorder or eating disorders are also prospectively associated with infertility, a bidirectional relationship is assumed. A special relationship exists between mental disorders and the main causes of ovulatory infertility, hypothalamic amenorrhea and polycystic ovary disease. The results of pilot studies support the assumption that psychotherapy may constitute an important component of the treatment of infertility.